How to position the patient? A meta-analysis of positioning in vestibular schwannoma surgery via the retrosigmoid approach - Vychopen, Martin; Arlt, Felix; Güresir, Erdem; Wach, Johannes (Frontiers in Oncology, 2023)
OBJECTIVE: Patient positioning is a matter of ongoing debate in the surgical treatment of vestibular schwannoma (VS). Main endpoints of this discussion are preservation of facial nerve functioning, extent of resection, and complications. In this meta-analysis, we aim to investigate the impact of patient positioning on VS surgery via the retrosigmoid approach. METHODS: We searched for eligible comparative trials on PubMed, Cochrane library, and Web of Science. Positioning groups were compared regarding facial nerve outcome, extent of resection, postoperative hydrocephalus, postoperative CSF leaks, perioperative venous air embolism, and perioperative mortality. Two groups of positions were defined, and the following positions were allocated to those groups: (1) Semi-sitting and Sitting-position; (2) Lateral position, supine position with extensive head rotation, lateral oblique (=Fukushima/Three-quarter prone), and park-bench position. RESULTS: From 374 full-text screenings, 7 studies met the criteria and were included in our meta-analysis comprising 1640 patients. Our results demonstrate a significantly better long-term (≥6 months) outcome of the facial nerve after VS surgery in the semi-sitting positioning (OR: 1.49, 95%CI: 1.03-2.15, p = 0.03). Positioning did not influence the extent of resection, rate of postoperative CSF leaks, and the presence of a postoperative hydrocephalus. Overall incidence of venous air embolisms was significantly associated with VS surgery in sitting positioning (OR: 6.77, 95% CI: 3.66-12.54, p < 0.00001). Perioperative mortality was equal among both positioning groups. CONCLUSION: Semi-sitting positioning seems to be associated with an improved facial nerve outcome after VS surgery via the retrosigmoid approach. Venous air embolisms are significantly more often observed among VS patients who underwent surgery in the sitting position, but the perioperative mortality is equal in both positioning groups. Both positioning groups are a safe procedure. Multicentric prospective randomized trials are needed to evaluate the risk-benefit ratio of each positioning in VS surgery via the retrosigmoid approach.